Effects of Baduanjin exercise on cognitive impairment in older adults: a systematic review and meta-analysis - Xiao-Gang Gong; Le-Peng Wang; Ling-Ling Yang; Feng Liu; Dao-Ning Zhang; A-Yuan Zhang; A-Yuan Zhang (Frontiers in Public Health, 2025)
BackgroundCognitive impairment in older adults poses a growing burden on global healthcare systems, especially in resource-limited communities. Baduanjin exercise, a low-cost traditional Chinese mind–body exercise, demonstrates considerable potential for assisting older adults in managing cognitive impairment. However, there is no consensus regarding its efficacy. This meta-analysis aimed to assess the feasibility and effectiveness of Baduanjin exercise in ameliorating cognitive impairment in older adults.MethodsRandomized controlled trials (RCTs) published through January 30, 2025, were searched in PubMed, Web of Science, Cochrane Library, Embase, ClinicalTrials.gov, and Chinese databases (CSTJ, CNKI, Wanfang). Two reviewers independently conducted trial selection, assessed methodological quality using the Cochrane Risk of Bias tool, and extracted data in accordance with PRISMA guidelines. Seven RCTs involving 539 community-dwelling older adults met the inclusion criteria.ResultsBaduanjin exercise significantly improved global cognitive function [mean difference (MD) = 2.15; 95% CI, 1.53 to 2.76; p < 0.00001], memory (standardized mean difference = 0.59; 95% CI, 0.38 to 0.80; p < 0.00001), executive function (SMD = 0.26; 95% CI, 0.07 to 0.44; p = 0.007), and physical health (MD = −0.86; 95% CI, −0.26 to −0.46; p < 0.00001). No included study reported adverse effects related to Baduanjin exercise.ConclusionThese findings indicate that Baduanjin exercise can effectively improve cognitive impairment in older adults. Nevertheless, further rigorously designed RCTs are required to confirm these findings.Systematic review registrationInternational Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY) under the registration number INPLASY202460007, https://inplasy.com/inplasy-2024-6-0007/.